2018
DOI: 10.1111/jvim.15135
|View full text |Cite
|
Sign up to set email alerts
|

A review of mycoplasma diagnostics in cattle

Abstract: Mycoplasma species have a global distribution causing serious diseases in cattle worldwide including mastitis, arthritis, pneumonia, otitis media and reproductive disorders. Mycoplasma species are typically highly contagious, are capable of causing severe disease, and are difficult infections to resolve requiring rapid and accurate diagnosis to prevent and control disease outbreaks. This review discusses the development and use of different diagnostic methods to identify Mycoplasma species relevant to cattle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 102 publications
(217 reference statements)
0
102
0
5
Order By: Relevance
“…All samples were obtained frozen and kept at freezing temperature for a period of up to one month to be processed. Freezing causes a decrease in the number of viable microorganisms that cannot be recovered in microbiological cultivation (Parker et al 2018). The low isolation rate obtained in the present study may be associated with freezing or thawing of milk samples, viable microbial load reduction, and the possibility of false-negative results in microbiological culture.…”
Section: Microbiological Analysismentioning
confidence: 62%
“…All samples were obtained frozen and kept at freezing temperature for a period of up to one month to be processed. Freezing causes a decrease in the number of viable microorganisms that cannot be recovered in microbiological cultivation (Parker et al 2018). The low isolation rate obtained in the present study may be associated with freezing or thawing of milk samples, viable microbial load reduction, and the possibility of false-negative results in microbiological culture.…”
Section: Microbiological Analysismentioning
confidence: 62%
“…For correct interpretation of this work, some points need to be clarified to the reader first. We used PCR, which is increasingly popular and accessible, but has important drawbacks for its interpretation at the herd level (Parker et al, 2018). For what are considered primary pathogens (viruses and M. bovis), detection at the herd level likely represents involvement in the outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of the detection methods for M. bovis showed that Real Time PCR was more specific and sensitive than immunohistochemistry (IHC). BPIV-3 and M. bovis persisted in chronic BRDC, unlike BRSV, suggesting permanent damage to the defense mechanisms in the lungs (Parker et al, 2018;Mehinagic et al, 2019).…”
Section: Resultsmentioning
confidence: 98%
“…(Taylor et al,2010). Mycoplasmas caused serious disease in cattle, with significant negative economic and welfare impacts (Parker et al, 2018). M. bovisis currently recognized as one of the most important and frequently isolated Mycoplasma species associated with cattle disease worldwide (Bednarek et al, 2012;Fox, 2012).…”
Section: Introductionmentioning
confidence: 99%